The Influence of Green Digital Marketing on Brand Image and Customer Loyalty - Putri, Anggun Rianda (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2026)
The rapid growth of digital business has encouraged companies to adopt environmentally responsible marketing strategies to strengthen their competitiveness. Green digital marketing has emerged as an approach that integrates sustainability values into online promotional activities. This study aims to examine the influence of green digital marketing on brand image and customer loyalty in the digital marketplace.This research applies a quantitative approach using a survey method. Data were collected from 150 respondents who actively use online shopping platforms and have interacted with digital promotional content from environmentally responsible brands. The sampling technique used was purposive sampling. Data analysis was conducted using multiple linear regression with the support of statistical software.The results show that green digital marketing has a significant positive influence on brand image. Furthermore, brand image also has a significant positive effect on customer loyalty. The findings indicate that green digital marketing indirectly contributes to strengthening customer loyalty through the improvement of brand image. These results confirm that integrating sustainability values into digital marketing strategies can enhance brand perception and encourage long-term relationships with customers.This study provides practical implications for digital business managers to design marketing campaigns that emphasize environmental responsibility as a strategic tool to build a strong brand image and loyal customer base.